SimNav: Simulink navigation of model clone classes - Rapos, Eric J.; Stevenson, Andrew; Alalfi, Manar H.; Cordy, James R. (2015 IEEE 15th International Working Conference on Source Code Analysis and Manipulation (SCAM), 2015)
SimNav is a graphical user interface designed for displaying and navigating clone classes of Simulink models detected by the model clone detector Simone. As an embedded Simulink interface tool, SimNav allows model developers to explore detected clones directly in their own model development environment rather than a separate research tool interface. SimNav allows users to open selected models for side-by-side comparison, in order to visually explore clone classes and view the differences in the clone instances, as well as to explore the context in which the clones exist. This tool paper describes the motivation, implementation, and use cases for SimNav.